Kebijakan Polresta Medan Terhadap Tindak Pidana Kejahatan yang Dilakukan Oleh Kelompok Geng Motor (Studi Kasus Polresta Medan) - Patar Maruli Simanjuntak (Universitas Sumatera Utara, 2019)
Abstract. Motorcycle gangis a group of young people who are members of a community of two-wheeled motorized vehicles. Gang was originally a component of adolescents who had the same goals. Starting from just looking for a new experience, then the actions of gang members over time become increasingly out of control and turn into criminal acts of violence and crime. For example, robbing and killing. In the scope of the Medan Police's policy problem against criminal acts of crime by motorcycle gang groups. The formulation of the problem in this study is what the causes of crime committed by motorcycle gangs in Medan Police are, how the Medan Police policy on crimes committed by motorcycle gang groups and what obstacles which are faced by Medan police in dealing with crimes which are committed by groups motorcycle gang are. The purpose of this study is to analyze and explain the factors that led to the crime which are committed by motorcycle gang groups in Medan Police, to identify and explain Medan Police's policy towards crimes which are committed by motorcycle gang groups, and to analyze and explain the obstacles in Medan Police dealing with crimes which are committed by motorcycle gang groups. This research is a normative juridical research that is a research that emphasizes legal science. The data collection techniques and tools are carried out by library studies and field studies that are obtained directly from the research location in the form of interviews with police officers. The data analysis carried out by qualitative methods. From the results of the study concluded: the motorcycle gangs in the law area of ​​Medan Police are very frightening to the public. Almost every night, motorcycle gangs convoy on the street carrying sharp machetes. This happens because of several factors including environmental factors, the influence of liquor, minimal formal education, and revenge factors. The policy which is carried out by Medan Police in tackling the level of crime committed by the motorcycle gang group is preventive in nature, namely, carrying out patrol activities, conducting raids on liquor sellers, and counseling in every school. Repressive efforts, namely, pursuing and arresting suspects, holding checks on suspects along with evidence, and then submitting documents to the District Prosecutor's Office for processing. Keywords: policies, crime, motorcycle gang